Child Poverty in a Regional Perspective: A Study of Sweden 1990 and 2010 - Daniel Rauhut; Svante Lingarde (European Regional Science Association (ERSA), 2013)
When welfare is analysed in Sweden the analysis is usually made at the national level; when the analysis is not done on the national level, the local level is in focus to illuminate differences between municipalities. Studies on poverty are no exception. The regional level contains a lot of information which is needed to understand the dynamics of poverty. Without this information it is difficult to fight or mitigate poverty. The previous research focusing on i) regional aspects of poverty and, at the same time, ii) child poverty is very limited. The aim of this paper is to analyse child poverty in Sweden 1990 and 2010 in a regional perspective. A multivariate cross-section OLS regression model will be used to estimate what factors causing child poverty in a regional perspective. The chosen method enables to control for a subset of explanatory variables and examine the effect of a selected independent variable when estimating the factors causing child poverty in a regional perspective. This study uses data collected from Statistics Sweden (SCB), the National Board of Social Welfare (Socialstyrelsen) and the National Labour Market Board (Arbetsformedlingen). The data used is regional macro data, which does not contain information on single individuals. The regional share of children living on economic assistance in Sweden is used as the dependent variable while the regional share of foreign born population, regional unemployment rate, the regional share of single parents, regional sickness leave, regional mean personal income and mean regional transfers per person are used as independent variables. The findings indicate that old industrial regions experience a high presence of child poverty. These regions experience an obsolete economic structure and an obstructed structural change in the economy. High unemployment, a high share of early retirement and sickness leave and relatively high welfare transfers to the population. The statistical analysis show that when the share of foreign born increases in the regional population, so do the regional share of children living on economic assistance; being unable to enter the labour market is the most probable reason. Higher incomes lower the regional share of children living on economic assistance.
Keywords: I32; J18; R59; 330; Child poverty; regional differences; deindustrialisation; income